Examination of ion concentration of ground water: Comparison of approximation methods - Gimesi, László (Acta Agraria Kaposváriensis, 2006)
During the recultivation of the slurry reservoirs of Pannonpower Co. feltthe need for examination (monitoring) of the soluted ion concentration in ground water. It had to take account of the fact that the water in question is close to the surface which could have effected to ecosystem on the surface. Ground water is strongly related to other sources of water like rivers, lakes, so the monitoring of the water flow had to be considered. Examination of the change in the ion concentration level of the water directly shows the water currents. The paper will display the data of examination with the help of a three dimensional digital graphical model which was chosen to cover the most of the data. Data collection is not an easy task especially if we aim to get multilevel informations, we were restricted to use mainly monitoring wells. Some of the data are based on estimation (approximation) procedures. To achieve the best possible approximation method we compared the efficiency of several methods, namely kriging, spline, inverse distance weighted, neural network.